2013
DOI: 10.1080/16506073.2012.756059
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Evaluation of a Brief Version of the Hyperventilation Questionnaire: The HVQ-B

Abstract: The fear of arousal sensations characterizes some anxiety disorders and is a core feature of an established risk factor for anxiety and related disorders (i.e. anxiety sensitivity; Taylor, 1999). Anxiety sensitivity (AS) refers to a fear of anxiety-related bodily sensations stemming from beliefs that these have catastrophic consequences. Interoceptive exposure (IE; repeated exposure to feared arousal sensations) has been shown to decrease AS. The 33-item Hyperventilation Questionnaire (HVQ; Rapee & Medoro, 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Following beverage consumption and absorption, they underwent a 3-min voluntary hyperventilation challenge. They then completed a measure (Rapee & Medoro, 1994; Sabourin et al, 2013) assessing their subjective experiences of somatic responses (e.g., pounding heart), cognitive responses (e.g., losing control), and affective responses (e.g., fear) to the hyperventilation challenge. High AS participants assigned to the placebo condition reported greater fear and catastrophizing responses to the hyperventilation challenge than did the low AS individuals assigned to the placebo condition.…”
Section: Basic Research On Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Following beverage consumption and absorption, they underwent a 3-min voluntary hyperventilation challenge. They then completed a measure (Rapee & Medoro, 1994; Sabourin et al, 2013) assessing their subjective experiences of somatic responses (e.g., pounding heart), cognitive responses (e.g., losing control), and affective responses (e.g., fear) to the hyperventilation challenge. High AS participants assigned to the placebo condition reported greater fear and catastrophizing responses to the hyperventilation challenge than did the low AS individuals assigned to the placebo condition.…”
Section: Basic Research On Asmentioning
confidence: 99%
“…In both the abovementioned trials of the three-session AS-targeted CBT intervention, we conducted additional analyses to examine the role of the running trials as interoceptive exposure. Specifically, those in the CBT condition completed a brief version (Sabourin et al, 2013) of the reactions to arousal-induction questionnaire used in the MacDonald et al’s (2000) study after each running trial. In analysis of this data from the Watt, Stewart, Birch, et al (2006), Watt, Stewart, Lefaivre, et al (2006) trial, at the onset of the running trials, high AS individuals reported greater somatic, affective, and cognitive reactions to the running trials than low AS individuals.…”
Section: Intervention Researchmentioning
confidence: 99%